Social Studies Education Curriculum Implementation in Tertiary Institutions in Nigeria - Edinoh, Kingsley; Wali-Essien, Ruth C. (Research Parks Publishers, 2023)
This paper focuses on examining the problems hindering the effective implementation of Social Studies Education Curriculum in the tertiary institutions in Nigeria. The paper gives insight into the different concepts that form its basis and further concludes that inadequate funding, shortage of Social Studies academic staff, inadequate instructional materials, inadequate infrastructural facilities, brain-drain and strike actions are some of the factors militating against the effective implementation of Social Studies Education curriculum in Nigeria’s tertiary institutions. It also highlights the increase in budgetary allocation to all Social Studies units in Nigeria’s tertiary institutions as a panacea for effective curriculum implementation.